Numerical and Experimental Study into forming of the longitudinal Externally Spline Sleeves by internally rotary Ballizing Process - Abd-Eltwab, Ayman Ali; Fahmy, Emad A.; El-Sheikh, Mohamed N.; Abu-Oqail, Ahmed M. I.; Elmetwally, Hammad T.; Abd-Elhalim, Eman S. M. (Manufacturing Technology Journal, 2025)
longitudinal externally splined parts have garnered increasing attention due to their critical role in power transmission across various industrial applications. This study explores the use of the internally rotating ballizing technique for manufacturing these components. The process was analyzed both experimentally and numerically through a mathematical model. The experimental investigation focused on key process parameters, including die rotational speed (50, 63, 80, 100, 125, 160, 200, 250, and 315 rpm), axial feed rate (0.13, 0.15, 0.18, and 0.21 mm/rev), interference between the balls and the tubular sample (cross in-feed: 2.5, 3.5, 4.5 and 5.5 mm), and initial tube thickness (4, 5, 6 and 7 mm). The study assessed the influence of these variables on the forming load and the quality of the produced longitudinal externally splined sleeves. A numerical model was developed to predict forming loads, and the findings indicated that these parameters significantly affect both (forming load and filling ratio). The optimal values for these variables were identified, and the numerical results showed a strong correlation with experimental findings. Keywords: Externally Splined Sleeves, rotary Ballizing Process, Numerical method, Experimental Study and forming load.
Keywords: Externally Splined Sleeves; rotary Ballizing Process; Numerical method; Experimental Study and forming load